Tecnología educativa aplicada a la informática en el proceso enseñanza aprendizaje en estudiantes de educación básica del Colegio Técnico República del Ecuador Machala provincia de El Oro 2015. - Romero Medina, Marjorie del Rocío (2016)
The present research tells us about the importance of educational technology applied to computing. As a j.clic and hot potatoes teaching and learning in basic education students Basic Education. As motivated students allows knowledge to surface as a responsibility to carry out tasks requiring the use of computer technology, however teachers go unnoticed to potential learning that could take place in interaction with educational programs, not proposed as one of the purposes of resource use that students learn computer files resource use that students learn computer files.